(untitled) (Asian Journal of Medical and Biological Research, 2021)
The present study was aimed to compare the production status and management practices of crossbred buffaloes between small scale and commercial farms in Bangladesh. The data were collected through personal interview from the individual respondent. The study revealed that duration of buffalo rearing was mostly practiced for more than two years. Various types of feed ingredients including rice straw, wheat straw, green grass, concentrate feed, cultivated fodder, tree leaves and unconventional feed resources were used for feeding buffaloes. In small scale, 83.34% farmers fed their buffalo in a group and 75% buffaloes reared under semi-intensive system while all buffaloes practiced individual feeding and reared under intensive system in commercial farms. The daily milk production, lactation length and yield of dam and birth weight of calves significantly (p<0.05) increased in commercial farm than small scale. However, the weaning age and weight was significantly (p<0.05) higher in village buffaloes than commercial farms. Similarly, age at 1st heat, 1st calving, services per conception and postpartum heat showed significantly (p<0.05) higher values in village than commercial farms. The major diseases of buffaloes in those areas were foot and mouth disease, black quarter, hemorrhagic septicemia, mastitis and anthrax. A proportion of 88.3% village farmers performed vaccination, in contrast, all buffaloes were vaccinated in commercial farms. The cost-return analysis discovered that rearing of buffalo in commercial farms was more profitable than rearing in small scale. Finally, the results revealed that productive and reproductive performances of buffaloes were better in commercial farms than small scale condition. Buffalo rearing is more profitable in commercial farms than small scale farming. Asian J. Med. Biol. Res. 2021, 7 (4), 323-331